Mourning for Tammuz: Prophecy and Projection in Ezekiel 8:14 - Morrow, William S. (Journal of Biblical literature, 2022)
While many commentators take Ezek 8:14 at face value, ancient Near Eastern parallels call this understanding into question. Both East and West Semitic sources indicate that mourning rituals for a goddess's dead consort were carried out in state-sponsored temples that symbolized the goddess. Since this does not accord with what is known about the Jerusalem temple in the early sixth century BCE, it is probable that the visionary writer of verse 14 has projected onto the temple observances for the dying god that did not belong to it. There are indications, however, that his mourning rites were also observed in less formal settings. Women were prominent participants in these popular rituals (as they were in funeral observances in general). It is likely, therefore, that the author of verse 14 knew of mourning rites for a dead god observed in Judah outside of the temple context. Since Ezekiel indicted illegitimate cultic activities that took place throughout the nation for defiling the central sanctuary, the vision of ritual mourning for Tammuz buttressed the prophet's claim that YHWH had decided to abandon the temple. As it is uncertain that women in Judah called the dead god "Tammuz," the use of that divine name may come from Ezekiel.